2017
DOI: 10.1002/mrc.4607
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing polarisation transfer to indazole and imidazole through signal amplification by reversible exchange to improve their NMR detectability

Abstract: The signal amplification by reversible exchange (SABRE) approach has been used to hyperpolarise the substrates indazole and imidazole in the presence of the co‐ligand acetonitrile through the action of the precataysts [IrCl(COD)(IMes)] and [IrCl(COD)(SIMes)]. 2H‐labelled forms of these catalysts were also examined. Our comparison of the two precatalysts [IrCl(COD)(IMes)] and [IrCl(COD)(SIMes)], coupled with 2H labelling of the N‐heterocyclic carbene and associated relaxation and polarisation field variation st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(83 citation statements)
references
References 48 publications
2
77
0
4
Order By: Relevance
“…[17] Thei dentity of the NHC ligand can also be modified to vary the lifetime of the active complex. [20] Thus far,n oq uantifiable correlation between the steric and electronic properties of the NHC ligands and polarization levels has been established;h owever, aromatic NHC ligands typically show improved performance. [18] Despite there being over 10 commercially available NHC ligands for the SABRE polarization of pyridine, [18,19] to date [IrCl(COD)(IMes)] remains the most impressive mediator of polarization transfer.T his optimum activity is common across ar ange of heterocyclic motifs, although rare examples exist for which this is not the case.…”
Section: Ancillary Ligand Effects On Sabre-complex Lifetimementioning
confidence: 99%
See 2 more Smart Citations
“…[17] Thei dentity of the NHC ligand can also be modified to vary the lifetime of the active complex. [20] Thus far,n oq uantifiable correlation between the steric and electronic properties of the NHC ligands and polarization levels has been established;h owever, aromatic NHC ligands typically show improved performance. [18] Despite there being over 10 commercially available NHC ligands for the SABRE polarization of pyridine, [18,19] to date [IrCl(COD)(IMes)] remains the most impressive mediator of polarization transfer.T his optimum activity is common across ar ange of heterocyclic motifs, although rare examples exist for which this is not the case.…”
Section: Ancillary Ligand Effects On Sabre-complex Lifetimementioning
confidence: 99%
“…[37] Substituted pyridyl substrates have proved to be particularly efficacious to SABRE and 1 Hp olarization levels of up to 50 %h ave been reported. [33] More complex substrates have also been shown to be amenable to SABRE with molecules with multiple ligation modes [20,38] and anumber of biologically significant molecules such as nicotinamide, [33] vitamin B 3 , [39] adenosine, [40] and the tuberculosis drug isoniazid showing good signal gains. [35,41] It has also been shown that polarization efficiency is decreased if no 4 J HH coupling is present in the active catalyst and asmaller 5/6 J HH coupling has to be utilized instead.…”
Section: Scope Of 1 H-sabre Polarizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As the rates of ligand exchange are relatively fast, substantial hyperpolarization levels can be produced in just a few seconds. SABRE has been demonstrated for a wide range of substrates which include pyridine and its derivatives, pyrazines, imidazoles, pyrazoles, pyridazines, pyrimidines, amino acids, diazirines, and acetonitrile . It hyperpolarizes not only their 1 H nuclei but the wide array of heteronuclei that they contain …”
Section: Introductionmentioning
confidence: 99%
“…[120] Importantly,S ABRE technique allows to hyperpolarized different 13 Ca nd 15 Nm olecules simultaneously. [182] Aw ide range of nitrogen-based heterocycles, [96,114,[121][122][123] diazirines, [116] sulfur heterocycles, [124] and drug molecules [125] have been hyperpolarized by using the SABRE technique, and these compounds could potentially become suitable molecular probes for hypoxia, [115,118,126] pH sensing, [127] and other processes [128,129] in vivo, although no in vivo application has yet been demonstrated( largely because SABRE has only been widely adopted within the past few years). [63]…”
Section: Homogeneous Signal Amplification By Reversible Exchangementioning
confidence: 99%